Understanding lack of development in early career teachers' practical knowledge of teaching speaking skills. (February 2019) - Webster, Simon
Abstract: Teacher learning is vital for educational institutions engaged in raising the quality of their programmes. Despite this, however, longitudinal research exploring when and how language teacher learning takes place is relatively limited with research mostly limited to studies into the effectiveness of formal teacher education programmes. This paper investigates the practical knowledge development of four early career English language teachers outside structured professional development programmes as they teach speaking skills to adult migrants. The extensive data, generated over a full academic year, indicate that practical knowledge growth was very limited during this period. Furthermore, the findings suggest a strong relationship between this absence of growth and the atheoretical nature of the teachers' practical knowledge. Such findings highlight the need for educational institutions to ensure mechanisms are in place which facilitate active and ongoing teacher engagement with public theory.